2013
DOI: 10.7736/kspe.2013.30.7.762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Muscle Function and Muscular Reaction of Knee Joint in the Twenties on the Whole Body Vibration Exercise

Abstract: This study investigated the effect of whole-body vibration on muscle function and muscular reaction in the knee joint. We recruited thirty healthy subjects and divided them into a training group, who experienced whole-body vibration, and a control group, who did not. The training group performed whole-body vibration exercises for 30 min per day, 3 days a week, for 8 weeks. We measured knee joint torque to estimate muscle strength and reaction, using BIODEX System 3. Knee joint peak torque and total work perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In recent years, both men and women have become interested in effective physical activity and healing while pursuing a healthy life. As a result of the increase in interest, studies on physical recovery programs such as fatigue recovery and muscle damage due to various sports and physical activities are actively being conducted [1,2]. Fatigue is a decline in mental and physical functions that occur accompanied by continuous or repeated mental and physical work and is an indicator of physiological stress, defensive response, or pathological precursor [3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, both men and women have become interested in effective physical activity and healing while pursuing a healthy life. As a result of the increase in interest, studies on physical recovery programs such as fatigue recovery and muscle damage due to various sports and physical activities are actively being conducted [1,2]. Fatigue is a decline in mental and physical functions that occur accompanied by continuous or repeated mental and physical work and is an indicator of physiological stress, defensive response, or pathological precursor [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been research and development of various exercise methods and machines as a result of interest in exercise for people of all ages to improve their health [1]. Whole body vibration has entered the limelight as a new exercise method in sports training and rehabilitation during the last decade [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Also there are some studies that investigated the effect of vibration stimulation on the muscle functions. Curry and Clelland reported that the vibration stimulation increased MVC (Maximum Voluntary Contraction) [ 11 ], and Kang et al reported that the systemic vibration exercise stimulated muscle nerves and shortened the muscle reaction time of the muscles [ 12 ].…”
Section: Introductionmentioning
confidence: 99%